Способ получения низкотемпературного пьезокерамического материала на основе цирконата-титаната свинца - Климов, В.В.; Селикова, Н.И.; Скирдина, И.К.; Бронников, А.Н.; Штонда, А.С. (Видавничий дім "Академперіодика" НАН України, 2007)
he technique of production of a lowemperature PZT-based piezomaterial is developed on the basis of the method of power action on the material (vibrating mill), together with the additive of
bismuth oxide. The sintering point is 850 ◦С, epsilon = 1160, tgdelta = 0.0045, Kр = 0.46, d31 = 100, Q = 740.